Correction: Carbazate-modified cross-linked dextran microparticles suppress the progression of osteoarthritis by ROS scavenging. (6th March 2023) - Ding, Yanfeng; Li, Zhimin; Hu, Wenwen; Feng, Xianjing; Chen, Ying; Yan, Guohua; Wang, Yonglin; Zhu, Bo; Yao, Wei; Zheng, Li; He, Maolin; Gao, Ming; et al.
Abstract : Correction for 'Carbazate-modified cross-linked dextran microparticles suppress the progression of osteoarthritis by ROS scavenging' by Yanfeng Ding, et al., Biomater. Sci ., 2021, 9, 6236–6250. ; https://doi.org/10.1039/D1BM00743B .